"We decided together": a qualitative study about women with HIV navigating infant-feeding decisions with the father of their children - Bakita Kasadha; Shema Tariq; Nell Freeman-Romilly; Catherine Pope; Angelina Namiba; Farai Nyatsanza; Lisa Hinton; Tanvi Rai (BMC, 2024)
Abstract Background The World Health Organization (WHO) recommends that women with HIV breastfeed for a minimum of one year. In contrast, United Kingdom (UK) guidelines encourage formula feeding, but breastfeeding can be supported under certain circumstances. Infant-feeding decisions often involve personal and social networks. Currently, little research addresses how individuals with HIV in high-income countries navigate infant-feeding decisions with the father of their children. Methods Semi-structured remote interviews were conducted with UK-based individuals with a confirmed HIV positive diagnosis who were pregnant or one-year postpartum, and two partners. Using purposive sampling, pregnant and postpartum participants were recruited through HIV NHS clinics and community-based organisations, and where possible, fathers were recruited via them. Data were analysed using thematic analysis and organised using NVivo 12. Results Of the 36 women interviewed, 28 were postpartum. The majority were of Black African descent (n = 22) and born outside the UK. The key factors in women navigating HIV and infant-feeding discussions with respect to their baby's father were the latter's: (1) awareness of woman's HIV status; (2) relationship with the woman; (3) confidence in infant-feeding decision; (4) support and opinion about woman's infant-feeding intentions. Most women made a joint decision with biological fathers when in a long-term (> one year) relationship with them. Single women tended not to discuss their infant-feeding decision with the father of their child, often for safety reasons. Conclusion Women in ongoing relationships with the father of their child valued their support and opinions regarding infant-feeding. In contrast, single women chose not to involve the father for reasons of privacy and safety. Clinical teams and community-based organisations should support mothers in discussing infant-feeding decisions regardless of relationship status. When appropriate, they should also support discussions with their partners, but remain sensitive to circumstances where this may put women at risk.